The VA, VCD, Raman and ROA spectra of tri-L-serine in aqueous solution - Jrgensen, V.; Jalkanen, Karl (IOP Publishing Ltd, 2006)
The structures of one conformer of the nonionic neutral and zwitterionic species of L-serinyl L-serinyl L-serine (SSS or tri-L-serine), together with its cationic and anionic species and the capped N-acetyl tri-L-serine N'-methylamide analog were optimized with density functional theory with the Becke 3LYP hybrid exchange correlation (XC) functional and the PW91 GGA XC functional and the 6-31G* and aug-cc-pVDZ basis sets. Subsequently, the vibrational absorption, vibrational circular dichroism, Raman and Raman optical activity spectra were simulated in order to compare them to experimentally measured spectra. In addition, we compare to previously reported studies for both structural determination and spectral simulations and measurements. A comparison of the various ways to treat the effects of the environment and solvation on both the structure and the spectral properties is thoroughly investigated for one conformer, with the goal to determine which level of theory is appropriate to use in the systematic search of the conformational space. In addition, the effects of the counterion, here Cl- anion, are also investigated. Here we present the current state of the art in nanobiology, where the latest methods in experimental and theoretical vibrational spectroscopy are used to gain useful information about the coupling of the nuclear, electronic and magnetic degrees of freedom and structure of tri-L-serine and its capped peptide analog with the environment.